LIFE CYCLE ASSESSMENT OF PAPER TOWEL AND ELECTRIC DRYER AS HAND DRYING METHOD IN THE UNIVERSITY OF MELBOURNE - Sri Hapsari Budisulistiorini (TEKNIK, 2007)
Nowadays products, services, or technologies are proactively evaluated toward environmental performance byusing the life cycle assessment (LCA). The assessment cover the whole life cycle from cradle to grave hence theproduct performance can be analyzed or compared with others for product development or for making adecision. The University of Melbourne currently installed towel dispenser by means of hand drying method inthe entire campus. As some has suggested that electric dryer will provide more sustainable service than papertowel, a LCA study will be a good approach for comparing both methods. The study utilizes SimaPro softwareto generated database for impact assessment. The assessment method used in this study is Eco-Indicator 99.From the LCA study, electric hand dryer performed better in most of indicators. Electric hand dryer istherefore recommended to be used in the entire campus of the University of Melbourne